Micro-/Meso-Scale Distinction and Horizontal Migration of Tintinnid (Ciliophora: Tintinnida) Assemblages in Three Regions Around the North Pacific Ocean - Feng, Meiping; Lin, Shiquan; Zhang, Wuchang; Wang, Chunsheng; Liu, Hongbin; Cheung, Shunyan; Li, Haibo; Stukel, Michael R.; Irving, John Paul; Li, Na (Frontiers in Marine Science, 2022)
We explored the relationships among different tintinnid populations on micro-, meso-, and basin-scales from three regions across the Pacific Ocean, including the Costa Rica Dome (CRD) in the Eastern Pacific Ocean, and the Celebes Sea (CS) and the Tokara Strait (TS) in the Western Pacific Ocean. We quantified the species occurrence, vertical and biogeographic distribution patterns, and morphological parameters of tintinnid assemblages. A total of 46 tintinnid species were observed, with more than half (63.0%) in common among three areas, accounting for 97.1% of the total abundances. The numerically abundant forms remained more or less the same set of species in the three areas. However, community structure analyses, in terms of species, Lorica Oral Diameter (LOD) size-classes, and genera, revealed clear distinctions among different regions, as well as among different water depths. A Lagrangian simulation of passive dispersal in ocean currents across the Pacific Ocean, supported the hypothesis that greater similarity between tintinnid populations in the CS and TS (relative to CRD) was related to ocean circulation linkages between the populations. A latitudinal decline of tintinnid species richness was observed, mainly as a result of a decline of redundant species and warm-water species in colder areas. These data provide information unique insight into population variability of microzooplankton communities on micro- to meso- and even large scales in the world oceans.